2018
DOI: 10.1002/cbin.11024
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CXCR4 regulates epithelial mesenchymal transition of NSCLC via the Hippo‐YAP signaling pathway

Abstract: CXCR4 has been shown to play a key role in the metastasis of non-small cell lung cancer (NSCLC). And CXCR may be associated with the Hippo-Yes kinase-associated protein (YAP) pathway, thus involving in the occurrence and progression of NSCLC. This study aims to investigate the effect of CXCR4 inhibition on epithelial-mesenchymal transition (EMT), invasion and migration of NSCLC cells via the Hippo-YAP pathway. QRT-PCR and Western blot were employed to detect CXCR4 expression in NSCLC cell lines. A549 and H1299… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Related proteins were detected to explore the mechanism of the EVA1A on EMT and apoptosis progression. Recent studies have provided enormous evidences suggesting that the Hippo signalling pathway can induce EMT 17,27,28 . Results revealed that compared with the control group, the Si‐ EVA1A group showed decreased N‐cadherin, vimentin and Bcl‐xL expression and increased Bax expression (Figure 6B).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Related proteins were detected to explore the mechanism of the EVA1A on EMT and apoptosis progression. Recent studies have provided enormous evidences suggesting that the Hippo signalling pathway can induce EMT 17,27,28 . Results revealed that compared with the control group, the Si‐ EVA1A group showed decreased N‐cadherin, vimentin and Bcl‐xL expression and increased Bax expression (Figure 6B).…”
Section: Resultsmentioning
confidence: 96%
“…YAP and TAZ are downstream effectors of the Hippo pathway and overexpressed in numerous cancers 16 . In recent years, several studies have found that the Hippo signalling pathway can promote tumour invasion and metastasis via EMT 16‐19 . And the molecular mechanism through which the Hippo pathway activates apoptosis is realized via p73 20‐22 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, CXCR4 was demonstrated to be heterogeneously expressed and upregulated upon stress, resulting in increased migration, which could be blocked by small molecule inhibitors to the Rho GTPases CDC42 and RAC [225]. Since RAC was shown to activate YAP in response to β-integrin signaling in MSC [63] and CXCR4 was reported to activate YAP in other cancers (i.e., non-small cell lung cancer [226]), it is possible that the metastatic spread of Ewing sarcoma cells with high CXCR4 may be supported by a mechanism involving YAP/TAZ.…”
Section: Yap/taz In Ewing Sarcomamentioning
confidence: 99%
“…Similar results were reported in the RT-CT treated mice ( Figure 5 B Lower). Altogether, the data indicate that ECAD and ZEB-1 are important for HCT116 chemotherapy-induced cellular plasticity, and that these mesenchymal features are modulated by CXCR4 inhibition [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chemokine receptor CXCR4 is overexpressed in colon cancer [10], where it represents a poor prognostic factor [11][12][13]. The CXCL12/CXCR4 axis also activates the EMT program in colorectal cancer, targeting the Wnt/β-catenin pathway [7,[14][15][16], and in multiple carcinomas such as pancreatic cancer [17], ovarian cancer [18] and non-small cell lung cancer (NSCLC) [19]. The aim of the study was to improve the efficacy of colon cancer standard therapy targeting CXCR4 with a new CXCR4 antagonistic peptide by reversing the EMT program [20].…”
Section: Introductionmentioning
confidence: 99%